Empowering Teachers with VR Technology for Immersive Learning Experiences - Sulisworo, Dwi; Maryani, Ika; Kusumaningtyas , Dian Artha; Rahmatika , Nuniek (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2024)
Background: The study explores insights from participants' discussions on the utilization of Virtual Reality (VR) technology in education and proposes recommendations to improve teacher competence in this domain. Contribution: The aim of this study was to identify training needs and educators' preferences in effectively integrating VR tools into their teaching practices. Method: This method involves collecting statements from participants, including their reflections on the benefits and challenges of using VR in education, as well as their suggestions for improvement. Results: Through thematic analysis, key findings emerged, showing strong interest among participants in utilizing VR to create immersive and engaging learning experiences. However, participants also expressed the need for additional training to address technical challenges, develop pedagogical strategies, and align the use of VR with curriculum requirements. Conclusion: Based on these findings, recommendations for follow-up training programs include providing comprehensive training on VR use, offering hands-on practice sessions, showcasing diverse VR applications, emphasizing strategies to increase student engagement, and building ongoing professional development opportunities. By addressing these recommendations, educators can improve their competence in utilizing VR technology to create a more effective and innovative learning environment.